The Effect of Board Capital and CEO Power on Corporate Social Responsibility Disclosures - Muttakin, Mohammad Badrul (Journal of business ethics, 2018)
This study examines the effect of directors’ human and social capital (i.e. board capital) on the level of corporate social responsibility (CSR) disclosures by drawing on insights from a resource-based view. It also investigates the effect of chief executive officer (CEO) power on this relationship. Data were obtained from annual reports of companies listed on the Dhaka Stock Exchange in Bangladesh from 2005 to 2013. We employ outside directors’ experiences and expertise as a proxy for board capital and measure CEO power using a ‘power index’ that comprises CEO duality, ownership, tenure and family CEO status. Results show that board capital is positively associated with CSR disclosure levels; however, CEO power is negatively associated with CSR disclosures and reduces the effect of board capital on CSR disclosures. Thus, we conclude that although board capital can improve CSR practices, CEO power can also inhibit these practices.